Mycotoxins and coccidiosis in poultry – co-occurrence, interaction, and effects - Gómez-Osorio, Luis-Miguel; Vasiljevic, Marko; Raj, Jog; Chaparro-Gutierréz, Jenny Jovana; López-Osorio, Sara (Frontiers in Veterinary Science, 2024)
Avian coccidiosis, a common disease caused by Eimeria species, results in significant losses in global poultry production. Mycotoxins are low-molecular-weight natural products (i.e., small molecules) produced as secondary metabolites by filamentous fungi and they have the potential to economically and significantly affect global poultry production. Little is known about the relationship between mycotoxins and avian coccidiosis, although they often co-occur in the field. This comprehensive review examines the intricate relationship between mycotoxins and avian coccidiosis, in particular how mycotoxins, including aflatoxins, ochratoxins, trichothecenes as well as Fusarium mycotoxins, compromise the health of the poultry flock and open the door to Eimeria parasites in the gut. In addition, this review sheds light on the immunosuppressive effects of mycotoxins, their disruption of cellular signaling pathways, and the consequent exacerbation of coccidiosis infections. The mechanisms of mycotoxin toxicity are also reviewed, emphasizing direct damage to intestinal epithelial cells, impaired nutrient absorption, inflammation, oxidative stress, and changes in the gut microbiota. Finally, the consequences for the prevention and treatment of coccidiosis when mycotoxins are present in the feed are discussed. This review emphasizes the need for effective management strategies to mitigate the combined risks of mycotoxins and coccidiosis and highlights the complexity of diagnosing and controlling these interrelated problems in poultry. The review advocates a holistic approach that includes strict feed management, disease prevention measures and regular monitoring to maintain the health and productivity of poultry against these significant challenges.